2020
DOI: 10.1159/000513012
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Hospitalizations among Sickle Cell Disease Patients with End-Stage Kidney Disease Initiating Dialysis

Abstract: <b><i>Background:</i></b> Sickle cell disease (SCD) is the most common inherited hematological disorder and a well-described risk factor for end-stage kidney disease (ESKD). Mortality and hospitalizations among patients with SCD who develop ESKD remain understudied. Furthermore, prior studies focused only on SCD patients where ESKD was caused by SCD. We aimed to describe mortality and hospitalization risk in all SCD patients initiating dialysis and explore risk factors for mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…2,3 Prior studies suggest the one-year mortality rate after initiating dialysis is higher in patients with SCD but early care by a nephrologist may decrease mortality. 4 Additionally, individuals with ESKD due to SCD (SCD-ESKD) are less likely to receive an arteriovenous fistula (AVF) when initiating haemodialysis (HD) 5,6 despite studies demonstrating improved survival when dialyzed with an AVF or graft. 7,8 Finally, referral for transplantation and transplantation rates are lower among individuals with SCD-ESKD despite the improved survival benefit of kidney transplantation.…”
mentioning
confidence: 99%
“…2,3 Prior studies suggest the one-year mortality rate after initiating dialysis is higher in patients with SCD but early care by a nephrologist may decrease mortality. 4 Additionally, individuals with ESKD due to SCD (SCD-ESKD) are less likely to receive an arteriovenous fistula (AVF) when initiating haemodialysis (HD) 5,6 despite studies demonstrating improved survival when dialyzed with an AVF or graft. 7,8 Finally, referral for transplantation and transplantation rates are lower among individuals with SCD-ESKD despite the improved survival benefit of kidney transplantation.…”
mentioning
confidence: 99%
“…Combining an ESA with hydroxyurea in SCD patients with CKD may allow more aggressive hydroxyurea dosing in high-risk patients and lead to a greater improvement in Hb concentration compared to ESA alone [121, 125]. One study noted a high erythropoietin dose was associated with an increased risk of mortality and hospitalizations in SCD patients with advanced stages of CKD [126]. Lastly, a new class of agents, the hypoxia inducible factor-prolyl hydroxylase inhibitors (HIF-PHIs) is being explored in patients with CKD with or without dialysis dependence.…”
Section: Ckd Managementmentioning
confidence: 99%
“…These investigators utilized the Centers for Medicare and Medicaid data between the years of 2005 and 2009 and additionally reported a lower death rate in SCD patients who received predialysis nephrology care. The higher mortality in patients with SCD on hemodialysis or peritoneal dialysis continues to be observed in follow-up studies [126, 131]; one study finds a significant association between the need for dialysis with higher mortality risk and hospitalization rates [126]. A recent analysis examining the US Renal Data System (USRDS) over a 19-year period demonstrated that despite prenephrology care, SCD patients on dialysis experienced significantly shorter survival when compared to non-SCD patients (7.0 vs. 12.4 years, respectively) [132].…”
Section: Ckd Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with SCD have more complications (specifically infections and thrombosis of dialysis access)‚ are admitted to hospital more frequently‚ and are less likely to be offered a kidney transplant. 16,17…”
Section: Introductionmentioning
confidence: 99%